A two-stage safety evaluation model for the red light running behaviour of pedestrians using the game theory. (March 2022) - Zhu, Dianchen; Sze, N.N.; Feng, Zhongxiang; Yang, Zhen
Highlights: Safety risk attributed to red light running behaviour of pedestrians is investigated. A game theoretical model is adopted to model the interferences between the decisions of pedestrian and driver. A bivariate ordered Probit model is adopted to model the risk of pedestrian-vehicle conflicts. Pedestrian gender, waiting time, walking speed and vehicle speed would affect the crossing decision of pedestrian and associated risk. Pedestrian walking speed, vehicle speed and vehicle type would affect the yield decision of driver and associated risk. Abstract: Red light running behaviour of pedestrians at the signalized crosswalks has been one of the major causes of pedestrian-vehicle crashes. Prior studies have identified the personal, environmental and traffic factors that affect the tendency of pedestrian to violate the pedestrian signal. However, it is rare that the safety consequences of red light running behavior of pedestrians are assessed. This paper aims to estimate the risk of pedestrian-vehicle conflicts attributed to the red light running behaviour of pedestrians using a two-stage modeling framework. In the first stage, interference of the decisions between driver and pedestrian at the crosswalks is modeled as a simultaneous two-player game, with which the errors of players' perceptions are incorporated using the quantal response equilibrium method. Then, the anticipations of pedestrian (to cross) and driver (to yield) in the game are estimated using the expected utility theory. In the second stage, risk of pedestrian-vehicle conflicts is modeled using the bivariate ordered Probit regression method, based on post encroachment time. Results indicate that both the pedestrian (i.e., gender and walking speed) and vehicle (i.e., speed, distance, and vehicle type) characteristics would affect the anticipations of driver and pedestrian, and therefore the risk of potential conflicts. For example, male and fast walking pedestrians have the higher expectations to cross. In contrast, vehicle speed increases with the anticipations of both pedestrian and driver to yield. Additionally, male have a higher risk of more severe conflicts. However, risk of more severe conflicts reduces when the walking speed and vehicle speed increase. Findings are indicative to the implementation of appropriate remedial measures including traffic management and targeted enforcement that can deter against the red light running behaviour of pedestrians. Hence, overall pedestrian safety can be improved in the long run.